Maladaptation to Climate Change Poses a Threat to Future Aquaculture Production - Lynne Falconer; Megan Rector; Suleiman O. Yakubu; Ramón Filgueira; Audun Iversen; Eirik Mikkelsen; Matthew Sprague; Elisabeth Ytteborg (Reviews in Aquaculture, 2026)
As the effects of climate change become more prominent and impacts intensify, the aquaculture sector must make decisions on adaptation strategies and implement actions that will reduce risks and increase resilience. However adaptation is complex, and there can be many consequences of action or inaction. One of the major risks is maladaptation, when an action that is introduced to minimize a negative effect makes the situation worse, increases vulnerability, or has other undesirable impacts. This study considers how climate change maladaptation can occur across six defined Aquaculture Maladaptation Outcomes: (1) Increased emissions of greenhouse gases, (2) Negative impact on farmed species, (3) Negative ecological or environmental impact at local, regional or international scale, (4) Negative social impact on individuals, communities, or the global population, (5) Negative economic impact on individuals, companies, or the global food market and (6) Reduced adaptive capacity of aquaculture systems. The study further explains that maladaptation could arise through different routes, often unintentionally and could occur at all stages in the production line and associated supply chain (e.g., feed production), such as the farm‐level or industry‐wide scale, threatening future food production and sustainability of the sector. The distinction between adaptation and maladaptation is not always clear, changing over time and influenced by different factors, so the adaptation‐maladaptation continuum is also discussed, as is the need for trade‐offs. Finally, seven recommendations are outlined to help advance adaptation to climate change in aquaculture.